PERSEPSI MASYARAKAT di SEKITAR DANAU TOBA TERKAIT RENDAHNYA TINGKAT KEBERHASILAN REBOISASI di DAERAH TANGKAPAN AIR DANAU TOBA - Frans Hutagalung; Budi Utomo; Afifuddin Dalimunthe (Program studi Kehutanan USU, 2015)
Reforestation is an activity that involves planting or regeneration of trees and other plants in the State forest areas and in other areas in other areas based on land-use plan designated as forest. The purpose of this study was to determine the public perception of the difficulty of successful reforestation activities in the Region Captive Air of Lake Toba. The data is taken from primary and secondary data. Primary data is information collected by reforestation activities in the villages, secondary data collected in the study site general conditions existing at the village government agencies which sampling method was done by purposive sampling ie sampling deliberately chosen. The results showed a lack of socialization in the extension of government reforestation activities, uncontrolled forest fires, lack of maintenance of seed that has been planted, the type of plant is less suitable.Keywords: Reforestation, Catchment area, purposive sampling, education, fire.